Design, synthesis and biological evaluation of novel benzodioxole derivatives as COX inhibitors and cytotoxic agents - Mohammed Hawash (BMC Chemistry, 2020)
Abstract Non-steroidal anti-inflammatory drugs are among the most used drugs. They are competitive inhibitors of cyclooxygenase (COX). Twelve novel compounds (aryl acetate and aryl acetic acid groups) were synthesized in this work in order to identify which one was the most potent and which group was most selective towards COX1 and COX2 by using an in vitro COX inhibition assay kit. The cytotoxicity was evaluated for these compounds utilizing MTS assay against cervical carcinoma cells line (HeLa). The synthesized compounds were identified using FTIR, HRMS, 1H-NMR, and 13C-NMR techniques. The results showed that the most potent compound against the COX1 enzyme was 4f with IC50 = 0.725 µM. The compound 3b showed potent activity against both COX1 and COX2 with IC50 = 1.12 and 1.3 µM, respectively, and its selectivity ratio (0.862) was found to be better than Ketoprofen (0.196). In contrast, compound 4d was the most selective with a COX1/COX2 ratio value of 1.809 in comparison with the Ketoprofen ratio. All compounds showed cytotoxic activity against the HeLa Cervical cancer cell line at a higher concentration ranges (0.219–1.94 mM), and the most cytotoxic compound was 3e with a CC50 value of 219 µM. This was tenfold more than its IC50 values of 2.36 and 2.73 µM against COX1 and COX2, respectively. In general, the synthesized library has moderate activity against both enzymes (i.e., COX1 and COX2) and ortho halogenated compounds were more potent than the meta ones.